2021
DOI: 10.1111/bph.15367
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of ursodeoxycholyltaurine to 7‐oxolithocholyltaurine serves as a biomarker of decreased 11β‐hydroxysteroid dehydrogenase 1 activity in mouse

Abstract: Background and Purpose: 11β-hydroxysteroid dehydrogenase 1 (11β-HSD1) regulates tissue-specific glucocorticoid metabolism, and its impaired expression and activity is associated with major diseases. Pharmacological inhibition of 11β-HSD1 is considered a promising therapeutic strategy. This study investigated whether alternative 7-oxo bile acid substrates of 11β-HSD1 or the ratios to their 7-hydroxy products can serve as biomarkers for decreased enzymatic activity. Experimental Approach: Bile acid profiles were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…If the BAs synthesized by the alternative pathway are inhibited, the proportion of 12-OH-BAs synthesized by the classical pathway will increase, which will further lead to a decrease in the liver's ability to respond to hepatic lipid homeostasis and the inflammatory state, and the degree of liver fibrosis was significantly associated with 12-OH-BAs (Jia et al, 2018;Jia et al, 2021;Xie et al, 2021). Along this line, we calculated the ratio of CA to CDCA because the ratio of CA to CDCA was selected to test if a possible shift in BA synthesis from the classical to the alternative BA pathway occurs in the liver (Chen et al, 2019;MahmoudianDehkordi et al, 2019;Weingartner et al, 2021). In the present investigation, we found that the BA synthesis in the ANIT-induced intrahepatic cholestatic model was still dominated by the classical pathway; however, the BA synthesis pathway in the BDL-induced extrahepatic cholestatic model shifted to the alternative pathway, and the proportion of TCA and TMCA in the two types of model mouse's liver supported this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…If the BAs synthesized by the alternative pathway are inhibited, the proportion of 12-OH-BAs synthesized by the classical pathway will increase, which will further lead to a decrease in the liver's ability to respond to hepatic lipid homeostasis and the inflammatory state, and the degree of liver fibrosis was significantly associated with 12-OH-BAs (Jia et al, 2018;Jia et al, 2021;Xie et al, 2021). Along this line, we calculated the ratio of CA to CDCA because the ratio of CA to CDCA was selected to test if a possible shift in BA synthesis from the classical to the alternative BA pathway occurs in the liver (Chen et al, 2019;MahmoudianDehkordi et al, 2019;Weingartner et al, 2021). In the present investigation, we found that the BA synthesis in the ANIT-induced intrahepatic cholestatic model was still dominated by the classical pathway; however, the BA synthesis pathway in the BDL-induced extrahepatic cholestatic model shifted to the alternative pathway, and the proportion of TCA and TMCA in the two types of model mouse's liver supported this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…The procedures for liver sample preparation and Western blotting have been previously described [66]. Briefly, liver samples (approximately 7 mg) were homogenized (30s, 6500 rpm, at 4˚C, using a Precellys-24 tissue homogenizer) in 450 μL RIPA buffer (50 mM Tris-HCl, pH 8.0, with 150 mM NaCl, 1.0% NP-40, 0.5% sodium deoxycholate and 0.1% sodium dodecyl sulfate) containing protease inhibitor cocktail and centrifuged (4 min, 16,000 × g, 4˚C).…”
Section: Analysis Of Protein Expression By Western Blottingmentioning
confidence: 99%
“…Earlier studies showed that human 11β-HSD1 is capable of metabolizing 7-oxo-cholesterol metabolites (Beck, Inderbinen, et al, 2019;Hult et al, 2004;Mitić et al, 2013;Schweizer et al, 2004) but also the secondary bile acid 7oxolithocholic acid (7oxoLCA) to ursodeoxycholic acid (UDCA) and to a lesser extent to chenodeoxycholic acid (CDCA) (Figure 1) (Mitić et al, 2013;Odermatt et al, 2011;Penno et al, 2013). A lack of this activity in guinea-pigs and in 11β-HSD1-deficient mice results in an accumulation of 7oxoLCA and its taurine conjugated form (Penno et al, 2013(Penno et al, , 2014Weingartner et al, 2021). A recent preclinical study employing three different transgenic mouse models of 11β-HSD1 deficiency and a model of pharmacological inhibition proposed the ratio of taurine conjugated UDCA (TUDCA) to 7oxoLCA (T7oxoLCA) in plasma samples as a biomarker to detect decreased 11β-HSD1 oxoreductase activity (Weingartner et al, 2021).…”
Section: Introductionmentioning
confidence: 99%